La Sardegna dei linguisti e la Sardegna per i turisti: consonanze e dissonanze discorsive a inizio Novecento - Stefanelli, Diego (Italianistica Debreceniensis, 2018)
The aim of this contribution is to tackle an already highly researched subject by adopting a fairly unprecedented perspective. I would like to concentrate on the representation of Sardinia in one of the most important historical moments for the construction of the image of the island in a modern perspective: the first decades of the twentieth century. I will try to make two apparently distant text types interact: tourist guides and travel reports written by linguists. I will focus on two prototype examples: on one hand the Reisebilder aus Sardinien by Max Leopold Wagner; on the other, the Touring Club Guide dedicated to Sardinia, written by Luigi Vittorio Bertarelli. My intent is to trace the similarities and differences of the two textual typologies in presenting a region at the time universally imagined (and narrated) as different, atypical and in any case "peculiar". In doing so, I will also try to highlight continuity and discontinuity with respect to the nineteenth-century representative methods.